Clinical characterization of glioblastoma patients living longer than 2 years: A retrospective analysis of two Italian institutions. Issue 3 (20th October 2020) - Anselmo, Paola; Maranzano, Ernesto; Selimi, Adelina; Lupattelli, Marco; Palumbo, Isabella; Bini, Vittorio; Casale, Michelina; Trippa, Fabio; Bufi, Alessandro; Arcidiacono, Fabio; Aristei, Cynthia
Abstract: Aim : Despite the advances in surgery and radio‐chemotherapy, the prognosis of glioblastoma (GBM) remains poor with about 13% of patients alive at 24 months. Methods : A total of 75 long‐term survivors (LTS), defined as alive at least 24 months from diagnosis, were retrospectively analyzed. Overall survival (OS) and recurrence‐free‐survival (RFS) were calculated and related to patient characteristics and treatment received. Results : Median age and Karnofsky performance status (KPS) were 56 years and 100%, respectively. After surgery (gross tumor resection‐GTR in 62, 83% patients), all LTS received concomitant temozolomide (TMZ) with radiotherapy and 70 (93%) adjuvant TMZ. Of these, 10 (13%) discontinued TMZ prior the completion of 6 cycles, 37 (49%) received 6 cycles and 23 (31%) >6 cycles. Sixty‐nine (92%) patients experienced a first tumor recurrence at a median time of 21 months. Of these, 32 (46%) were submitted to a second surgery, 34 (49%) to other no‐surgical treatments and 3 (5%) only supportive care. At multivariate analysis, OS was significantly improved by second surgery after first recurrence ( P = 0.0032) and by cycles of adjuvant TMZ > 6 versus ≤6 ( P = 0.05). More than six cycles of TMZ significantly conditioned also first RFS ( P = 0.011) and second RFS ( P = 0.033). Conclusion : The large majority of LTS had <65 years, had a high KPS and received GTR. OS and RFS resulted significantly related to an extended administration of adjuvant TMZ (>6 cycles) and a second surgery in case of recurrence. Abstract : In a period of 17 years, 595 GBM patients were treated; 75 were classified as LTS (i.e. alive at least 24 months from diagnosis), 13 were VLTS with at least 5 years of survival. This retrospective study describes our clinical experience of LTS identifying factors predictive of survival.